Plasma-catalysis chemical looping CH4 reforming with water splitting using ceria supported Ni based La-perovskite nano-catalyst. (July 2019) - Ranganathan, Rajagopalan V.; Jony, Bodiuzzaman; Fondriest, Steven M.; Liu, Zhongqi; Wang, Ruigang; Uddi, Mruthunjaya
Graphical abstract: Highlights: Plasma assisted chemical looping reforming and water splitting. Higher conversion and yield with plasma-assisted looping over 150–800 °C. Significant H2 production by plasma water splitting over 150–400 °C. Material changes at 1000 °C affects plasma catalysis at lower temperatures. Abstract: Chemical Looping reactions have the advantage of producing useful chemicals, with minimal energy penalty while achieving Carbon Capture Sequestration (CCS). We present the results of Plasma Catalytic (PC) CH4 reforming reduction step coupled with PC water splitting oxidation step to produce hydrogen. We use CH4 +CO2 flow reduction step with nano-powder, 50:50 mass ratio of La0.9 Ce0.1 NiO3 perovskite with CeO2 solid mixture as catalyst with Oxygen Carrier (OC) combination. The material is oxidized with H2 O+Ar during the oxidation step leading to H2 production by water splitting. The primary goal is to study the plasma-assisted reforming and water splitting, with the purpose of achieving reactions at low temperatures (150–400 °C). Water splitting H2 production (24–30 μmole/g total) and CH4 reforming (14–43 % conversion) were observed in the temperature range of 150–400 °C, while no such reactions were observed without plasma in this low temperature range, with just the oxygen carrier nano-materials. Substantial enhancements were also observed at higher temperatures.